1989
DOI: 10.1002/ange.19891010205
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Biosynthese von Antibiotica

Abstract: Die Feinheiten der chemischen Synthesen, die von lebenden Zellen beim Aufbau komplexer organischer Naturstoffe ausgefuhrt werden, lassen sich durch Markierung mit stabilen Isotopen in Verbindung mit hochentwickelten 2D-und Mehrquanten-NMR-Analysenmethoden detailliert untersuchen. Mechanistische Einzelheiten werden durch Aufklarung der ,,kryptischen" Stereochemie biosynthetischer Reaktionen mit Hilfe stereospezifischer Isotopenmarkierung enthullt. Die Analyse blockierter Mutanten und das Klonieren von Biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 186 publications
0
6
0
Order By: Relevance
“…Because of differences in dilution factors in different experiments their data could also be interpreted to indicate that [amide- 15 N]glutamine and [ 15 N]glutamate are comparable nitrogen sources in rifamycin biosynthesis. Furthermore, in studies comparing [amide- 15 N]glutamine, [ 15 N]glutamate, and 15 NH 4 Cl as nitrogen sources in ansatrienin biosynthesis we were unable to identify any one of these substrates as the preferred source of the mC 7 N unit nitrogen 21b. Thus, the question of the proximate source of the nitrogen in AHBA must await the purification of aminoDAHP synthase and more detailed studies on this enzyme.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Because of differences in dilution factors in different experiments their data could also be interpreted to indicate that [amide- 15 N]glutamine and [ 15 N]glutamate are comparable nitrogen sources in rifamycin biosynthesis. Furthermore, in studies comparing [amide- 15 N]glutamine, [ 15 N]glutamate, and 15 NH 4 Cl as nitrogen sources in ansatrienin biosynthesis we were unable to identify any one of these substrates as the preferred source of the mC 7 N unit nitrogen 21b. Thus, the question of the proximate source of the nitrogen in AHBA must await the purification of aminoDAHP synthase and more detailed studies on this enzyme.…”
Section: Discussionmentioning
confidence: 94%
“…However, this still leaves unexplained how AHBA is formed via the shikimate pathway. While it was first thought that the nitrogen is attached to C-3 of, e.g., 3-dehydroshikimic acid (DHS),5a the analysis of labeling patterns in mitomycin 7b and 13 C− 13 C coupling patterns in geldanamycin, naphthomycin 18 and ansatrienin revealed that the nitrogen is actually linked to the carbon corresponding to C-5 of shikimic acid. This led Hornemann et al 7b.…”
mentioning
confidence: 99%
“…Another member of this subgroup, graG, has recently been shown by inactivation experiments to be involved in the biosynthesis of the 2,3,6-trideoxysugar, Lrhodinose. 2 The second subgroup (Fig. 4) …”
Section: -Amino-5-hydroxybenzoic Acid Synthasementioning
confidence: 99%
“…Therefore, the development of novel methods for the preparation of carboxylic acids is of long-standing interest to organic chemists because of the importance of these compounds in chemistry and biology. [1] Carboxylic acids are versatile building blocks in the synthesis of natural products, pharmaceuticals, agricultural chemicals, polymers and dyes. [2] Traditionally, carboxylic acids are synthesized from olefins or alkynes by ozonolysis, [3a-c] or by a twostep process involving dihydroxylation and oxidative cleavage of diols with NaIO 4 and oxidants.…”
mentioning
confidence: 99%